Pengaruh Keadilan Pajak, Biaya Kepatuhan dan Tarif Pajak terhadap Persepsi Wajib Pajak Mengenai Penggelapan Pajak di Kantor Pelayanan Pajak Pratama Maros - Jumriah, Jumriah; Ilham, Ilham; Ka, Veronika (PT Bone Jaya Kreatif, 2023)
The purpose of this study was to determine how the perception of taxpayers about tax avoidance at KPP Pratama Maros is influenced by tax rates, compliance costs, and tax justice. Quantitative research is the subject of this research. This study uses primary data and secondary data, which were collected through questionnaires and literature study of 400 taxpayers of KPP Pratama Maros as the research sample. SPSS 20 was used to perform multiple linear regression analysis as a data analysis method. The findings show that taxpayers' perceptions of tax avoidance are significantly influenced by tax equity. The costs associated with compliance have a significant impact on how taxpayers perceive tax evasion. Taxpayers' perception of tax avoidance is significantly influenced by tax rates. At KPP Pratama Maros, taxpayers' perceptions of tax avoidance are significantly influenced by tax equity, compliance costs, and tax rates. Improving the socialization and education of taxpayers can reduce tax avoidance.